2018
DOI: 10.3389/fevo.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Photosymbiosis Between Fraginae Bivalves and Symbiodinium Using Phylogenetics and Stable Isotopes

Abstract: Photosymbiotic associations between heterotrophic hosts and photosynthetic algae play crucial roles in maintaining the trophic and structural integrity of coral reef ecosystems. The marine bivalve subfamily Fraginae contains both non-symbiotic and photosymbiotic lineages, making it an ideal comparative system to study the origin and evolutionary adaptations of photosymbiosis. The symbiotic species exhibit unique morphological adaptations to photosymbiosis. However, the basic biology of these photosymbiotic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…In contrast with the relatively labile shell and mantle adaptations, it is possible that the evolution of host metabolomic and developmental Therefore, it is highly likely that host-symbiont interactions and reliance vary greatly among hostsymbiont pairs, depending on symbiont types, as well as degrees of host adaptations. Li et al 2018 [8] summarized known symbiont diversity in giant clams and showed that several fragine species harbor symbionts from the genus Cladocopium, which also occupies cnidarians, giant clams, and foraminifera. However, this by no means captured the full spectrum of potential symbiont diversity in photosymbiotic bivalves, especially when new host species are discovered regularly (e.g., [34]).…”
Section: Implications On Photosymbiosis Evolutionmentioning
confidence: 99%
“…In contrast with the relatively labile shell and mantle adaptations, it is possible that the evolution of host metabolomic and developmental Therefore, it is highly likely that host-symbiont interactions and reliance vary greatly among hostsymbiont pairs, depending on symbiont types, as well as degrees of host adaptations. Li et al 2018 [8] summarized known symbiont diversity in giant clams and showed that several fragine species harbor symbionts from the genus Cladocopium, which also occupies cnidarians, giant clams, and foraminifera. However, this by no means captured the full spectrum of potential symbiont diversity in photosymbiotic bivalves, especially when new host species are discovered regularly (e.g., [34]).…”
Section: Implications On Photosymbiosis Evolutionmentioning
confidence: 99%
“…better isotopic metrics, Therefore, it is highly likely that host-symbiont interactions and reliance vary greatly among hostsymbiont pairs, depending on symbiont types, as well as degrees of host adaptations. Li et al 2018 [8] summarized known symbiont diversity in giant clams and showed that several fragine species harbor symbionts from the genus Cladocopium, which also occupies cnidarians, giant clams, and foraminifera. However, this by no means captured the full spectrum of potential symbiont diversity in photosymbiotic bivalves, especially when new host species are discovered regularly (e.g., [63]).…”
Section: Implications On Photosymbiosis Evolutionmentioning
confidence: 99%
“…Giant clams acquire a considerable amount of organic carbon through photosymbiosis [10]. All species in the subfamily possess symbiotic algae from the family Symbiodiniaceae (also found in symbiosis with corals), mostly placed in the genera Symbiodinium, Cladocopium, and Durusdinium [8,11]. The giant clam harbors extracellular symbionts within a tubular network derived from the digestive system that extends into the mantle tissue [12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations